Validation of Assay Indicating Method Development of Simvastatin in Bulk and its Tablet Dosage form by RP-HPLC - Nalini Kanta Sahoo, Madhusmita Sahu, P. Srinivasa Rao, R.S.Vineela, J.N.V. Indira Devi, N.Sandhya Rani, Goutam Ghosh (Journal of Applied Pharmaceutical Science, 2014)
A novel, simple and economic reverse phase high performance liquid chromatography (RP-HPLC) method has been developed for the estimation of Simvastatin in bulk and tablet dosage form with greater precision and accuracy. Separation was achieved on Develosil ODS HG-5 RP C18, (150cmx4.6mm i.d. 5µm) column in isocratic mode with mobile phase consisting of acetonitrile :phosphate buffer(pH 3.0) (85:15) with a flow rate of 1 mL/min. The detection was carried out at 236 nm. The retention time of Simvastatin was found to be 5.84 min. The method was validated as per ICH guidelines.Linearity was established for Simvastatin in the range 10 – 100 μg / ml with R2 value 0.99. The percentage recovery of Simvastatin was found to be in the range 99.19-99.67 %. The high recovery and low relative standard deviation confirm the suitability of the proposed method for the estimation of the drug in bulk and tablet dosage forms. The LOD and LOQ were found to be 0.341 and 1.023 µg/ml respectively.Validation studies demonstrated that the proposed RP-HPLC method is simple, specific, rapid, reliable and reproducible for the determination of Simvastatin for Quality Control level.
Keywords: RP-HPLC,Simvastatin,Quality control level.